2006
DOI: 10.21273/horttech.16.4.0649
|View full text |Cite
|
Sign up to set email alerts
|

Northern Field Production of Leaf and Romaine Lettuce using a High Tunnel

Abstract: A high tunnel environment was evaluated for production of leaf (`Two Star') and romaine (`Parris Island Cos') lettuce (Lactuca sativa) in a northern location (lat. 64°49'N). Ten plantings were made 1 week apart from May to August. Averaged over the season, the air temperature was 1.5 °C and the soil 0.8 °C higher in the high tunnel than the field. `Two Star' planted on 3 Aug. and harvested on 16 Sept. produced higher yield (P < 0.001) in the tunn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 16 publications
1
31
0
1
Order By: Relevance
“…The crop types in this study appeared to mature at different times and Asian greens grew to a suitable size for salad mix earlier than spinach or lettuce. Certain leafy green cultivars may have slower growth than others when temperatures are below optimal levels (Mansour and Raab, 1996;Rader and Karlsson, 2006;Smith et al, 2011). As a result, the mixed stand of leafy green vegetables grown in this experiment made it difficult to harvest all cultivars at their optimal market maturity.…”
Section: Discussionmentioning
confidence: 99%
“…The crop types in this study appeared to mature at different times and Asian greens grew to a suitable size for salad mix earlier than spinach or lettuce. Certain leafy green cultivars may have slower growth than others when temperatures are below optimal levels (Mansour and Raab, 1996;Rader and Karlsson, 2006;Smith et al, 2011). As a result, the mixed stand of leafy green vegetables grown in this experiment made it difficult to harvest all cultivars at their optimal market maturity.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, lettuce plants were grown in open field and high tunnels to provide contrasting growing conditions. High tunnels, which are unheated and passively ventilated production structures, have been widely used in Asia and Europe and are increasingly being used in the US (Lamont et al, 2003;Spaw and Williams, 2004;Wells, 1996) tunnels are known to produce higher yields and better quality of crops by extending their growth period and by providing protection from various adverse factors (Hodges and Brandle, 1996;Rader and Karlsson, 2006). Although studies on green leafy vegetables have indicated higher antioxidant capacity and phenolics in response to open field cultivation relative to high tunnels, the results have been variable in regards to species, growth stage and specific phenolic compounds (Zhao et al, 2007).…”
Section: Research Reportmentioning
confidence: 99%
“…High tunnel use throughout the United States is on the increase as a result of earlier crop production and the opportunity to exploit local markets with regionally grown produce (Carey et al, 2009;Knewtson et al, 2010). In regions with short growing seasons, extending the production period can have significant economic benefit (Rader and Karlsson, 2006;Rowley et al, 2010;Waterer, 2003). Tomatoes (Solanum lycopersicum L.) are the most commonly grown high-tunnel crop because early, local, high-quality tomatoes have a high value in the market (Knewtson et al, 2010;Ward et al, 2011).…”
mentioning
confidence: 99%